2011
DOI: 10.4103/0970-9185.81835
|View full text |Cite
|
Sign up to set email alerts
|

Post operative analgesia after incisional infiltration of bupivacaine v/s bupivacaine with buprenorphine

Abstract: Introduction:Opioid receptors have been demonstrated in the peripheral nerve endings of afferent neurons. Blockade of these receptors with peripherally administered opioid is believed to result in analgesia.Aim:To evaluate whether buprenorphine added to bupivacaine for wound infiltration can enhance post-operative analgesia via peripheral mechanisms.Materials and Methods:Forty ASA I and II adult patients scheduled for open donor nephrectomy were enrolled in this randomized double blind prospective study. In gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…[11] performed incisional infiltration of bupivacaine versus bupivacaine with buprenorphine in 40 open donor nephrectomy patients. They concluded that addition of buprenorphine to local anesthetic significantly prolonged the time to 1 st rescue analgesic demand and total consumption of rescue analgesic in 24 hours thus providing evidence in support of the existence of peripheral opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…[11] performed incisional infiltration of bupivacaine versus bupivacaine with buprenorphine in 40 open donor nephrectomy patients. They concluded that addition of buprenorphine to local anesthetic significantly prolonged the time to 1 st rescue analgesic demand and total consumption of rescue analgesic in 24 hours thus providing evidence in support of the existence of peripheral opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…However, differences in pain intensity rating (using a numerical rating scale) between the two buprenorphine-treated study groups were not statistically significant. The peripheral effects of buprenorphine were assessed by Mehta et al, who used buprenorphine to infiltrate the surgical wound following elective nephrectomy [21]. They reported significantly lower VAS scores in patients who had the wound anaesthetized by infiltration of a solution of bupivacaine with a buprenorphine adjuvant compared to infiltration with bupivacaine alone.…”
Section: Discussionmentioning
confidence: 98%
“…There is lot of evidence for presence of peripheral opiod receptors and their role in alleviation of pain. [721] Stein et al . and Puhler et al .…”
Section: Discussionmentioning
confidence: 99%
“…conducted a study where they infiltrated incisional wound with bupivacaine and buprenorphine and concluded that ‘Addition of buprenorphine to the local anaesthetic significantly prolongs post operative analgesia’, thus providing evidence in support of the existence of peripheral opioid receptors. [7] Hence, we thought of using opioids for haematoma block.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation